Characterization of edaphic arthropods in two areas with different vegetation cover in the central region of Rio Grande do Sul - Milagre, Jocimar Caiafa; Dick, Grasiele; Mendes, Lucas José; Paz, Thaynara Diuliane Carvalho; Stangarlin, Mauricio Pegoraro; Santos, João Antônio Rodrigues; Schumacher, Mauro Valdir (Revista Ecologia e Nutrição Florestal - ENFLO, 2022)
Edaphic arthropods are organisms of great ecological importance and their dynamics in leaf litter and soil can be influenced by the type of vegetation cover. We aimed to characterize and compare abundance, richness and diversity and uniformity indices of edaphic arthropods in an area occupied by bamboo (BM) and a reforested area (RF), located in the central region of Rio Grande do Sul state, south Brazil. The hypothesis of this study is that there will be greater abundance, richness, diversity and uniformity of organisms in the RF area. The collection of soil fauna was performed by sampling the arthropods present at the soil-leaf litter interface using Provid collectors at four points in each study area. There were high levels of abundance and richness of arthropods in both areas of the study, and the orders Collembola, Coleoptera, Hymenoptera and Diptera were the most representative. The predicted hypothesis was refuted, since the RF area had a smaller number of individuals and the same richness as the BM area. BM area showed greater abundance of individuals of the order Diptera when compared to the RF area, and for the other orders there were no significant differences. Additional studies considering the physical and chemical properties of the soil and the litter composition may help to better understand the relationship between edaphic arthropods and vegetation cover in these areas, besides the bioindicator role of these organisms.